(untitled) (Advancements in Homeopathic Research, 2025)
Aim: To know the impact of homoeopath ic medicines in managing Trichotillomania. Place and Duration of Study: National Ho moeopathy Research Institute in Mental Health, Kerala, between July 2021 and July 2022. Methodology: A 25-year-old female with Trichotillomania was assessed using standard ized tools including the MGH Hair Pulling Scale. Repertorization was performed with RA DAR Opus software, and individualized reme dies were prescribed with follow-up assessments. Results: The patient showed marked reduction in hair-pulling frequency and anxiety, with signifi cant improvement documented across follow-ups. Modified Naranjo Criteria confirmed causal attribu tion of improvement to homoeopathic intervention. Conclusion: This case highlights the therapeutic po tential of individualized homeopathic treatment in Trichotillomania. Further controlled studies are war ranted.